Strengthening accountability for tuberculosis policy implementation in South Africa: perspectives from policymakers, civil society, and communities - Helene-Mari van der Westhuizen; Janet Giddy; Renier Coetzee; Goodman Makanda; Phumeza Tisile; Michelle Galloway; Siyavuya Bunyula; Ingrid Schoeman; Ruvandhi R. Nathavitharana (BMC, 2024)
Abstract Background Translating health policy into effective implementation is a core priority for responding effectively to the tuberculosis (TB) crisis. The national TB Recovery Plan was developed in response to the negative impact that the COVID-19 pandemic had on TB care in South Africa. We aimed to explore the implementation of the TB Recovery Plan and develop recommendations for strengthening accountability for policy implementation for this and future TB policies. Methods We interviewed 24 participants working on or impacted by TB policy implementation in South Africa. This included perspectives from national, provincial, and local health department representatives, civil society, and community representatives. In-depth interviews were conducted in English and isiXhosa and we drew on reflexive thematic methods for analysis. Results Participants felt that there was potential for COVID-19 innovations and urgency to influence TB policy development and implementation, including the use of data dashboards. Implementation of the TB Recovery Plan predominantly used a top-down approach to implementation (cascading from national policy to local implementers) but experienced bottlenecks at provincial level. Recommendations for closing the TB policy-implementation gap included using phased implementation and enhancing provincial-level accountability. Civil society organisations were concerned about the lack of provincial implementation data which impeded advocacy for improved accountability and inadequate resourcing for implementation. Community health workers were viewed as key to implementation but were not engaged in the policy development process and were often not aware of new TB policies. At local level, there were also opportunities to strengthen community engagement in policy implementation including through community-led monitoring. Participants recommended broader multi-stakeholder engagement that includes community and community health worker representatives in the development and implementation phases of new TB policies. Conclusions Communities affected by TB, with the support of civil society organisations, could play a bigger role in monitoring policy implementation at local level and need to be capacitated to do this. This bottom-up approach could complement existing top-down strategies and contribute to greater accountability for TB policy implementation.